Side effects and complications of injection laryngoplasty for treatment of congenital type 1 laryngeal clefts. (April 2020) - Ramazani, F.; Isaac, A.; Johannsen, W.; El-Hakim, H.
Abstract: Introduction: Injection laryngoplasty (IL) is a brief, minimally invasive procedure involving injection of agents to augment the interarytenoid space. It was initially described as a diagnostic and temporizing measure for management of type one laryngeal clefts (LC1) and associated swallowing dysfunction (SwD), but more gradually it is being proposed as a definitive treatment modality. However, the morbidity of this treatment for LC1 remains under-investigated. This study sought to determine the morbidities associated with IL as a treatment modality for LC1 and associated SwD. Method: Single centre retrospective review of a prospective surgical database of one Pediatric Otolaryngologist at a tertiary care center. Participants included pediatric patients with an endoscopic diagnosis of LC1, treated with IL between 2000 and 2018—excluding those with concurrent upper airway anomalies. Patient charts were reviewed for demographic information, immediate post-op complications (within the first 14 days following IL), and subsequent management. Results: Out of 85 consecutive, eligible patients, 12 were excluded (5 subglottic stenosis, 6 laryngomalacia, and one tracheomalacia). Of the 73 included patients, 42 were male and 31 females. The median age at IL was 29 months (range 1–132, interquartile range of 38 months). All IL procedures in this study utilized hyaluronic acid derivatives. From this series, 13 patients experienced post-operative complications. The complications encountered were respiratory distress ( N = 5), croup-like cough ( N = 6), and stridor ( N = 6). These complications were either self-limiting ( N= 9), managed by systemic or inhaled steroids ( N = 4), or admitted to hospital for monitoring ( N= 3). One case (augmented with dextranomer and hyaluronic acid) required intubation, repeat endoscopy, and drainage of seroma. Conclusion: IL was followed by respiratory morbidity in nearly two in ten of this series of consecutive patients. All the morbidities occurred in association with one injection product. Parents should be counselled appropriately about potential morbidities associated with this procedure.